Introduction: Ethnography, Moral Theory, and Comparative Religious Ethics - Ranganathan, Bharat (Journal of religious ethics, 2017)
Representing a spectrum of intellectual concerns and methodological commitments in religious ethics, the contributors to this focus issue consider and assess the advantages and disadvantages of the shift in recent comparative religious ethics away from a rootedness in moral theory toward a model that privileges the ethnography of moral worlds. In their own way, all of the contributors think through and emphasize the meaning, importance, and place of normativity in recent comparative religious ethics.